Homeopathy and Heat Stroke A Gentle Approach to Healing (Homoeopathy for All, 2024)
Heat stroke is a potentially fatal  medical condition marked by a  sudden rise in body temperature,  frequently above 104°F (40°C),  and malfunctioning of the central  nervous system. Rapid cooling and  supportive care are the mainstays  of conventional treatment, although  complementary and alternative  therapies like homeopathy are  gaining popularity. An extensive  analysis of homeopathy's  application in the treatment  of heat stroke is given in this  article. When treating heat stroke,  homeopathy takes a comprehensive  approach, taking into account each  patient's unique symptoms and  constitutional makeup. The patient's  particular symptoms, such as a  high fever, headache, confusion,  and dehydration, are taken into  consideration while choosing a  course of action. Clinical research  and case studies indicate that  homeopathic remedies can help  reduce symptoms, speed up recovery,  and avoid problems related to illness  when used promptly and effectively.
Keywords: Heat Stroke; Homeopathic Medicine; Homeopathic Medicine , Remedies; Headache; Dehydration; Central Nervous System; Clinical Research